The Effects of Extensive Journal Writing on the Vietnamese High-School Students' Writing Accuracy and Fluency - Vu Phi Ho Pham; Tuyen Thi Thanh Tran; Ngoc Hoang Vy Nguyen (National Research University Higher School of Economics, 2022)
The innovation of an extensive journal writing approach has made a big difference in the field of teaching academic writing. Previous studies found mixed results relating to whether journal writing could help students enhance their writing accuracy. The purpose of the current study is to investigate whether extensive journal writing (EJW) affects EFL high school students' writing accuracy and fluency in the writing classroom. Sixty students in one of the high schools located in Tra Vinh city participated in the study. The quasi-experimental study was conducted in ten weeks. The participants were divided into two groups, namely the control group and the experimental group. Students' writing papers, including pre-tests and post-tests, were collected for data analysis. Inter-raters were employed for analytic rating scales and written errors analysis. The results show that extensive journal writing had significant effects on the students' writing performances compared to those of students in the control group. Additionally, the number of words written in the students' post-test was increasing. The current study's findings were innovative to the body of literature as the EJW could help students enhance their writing performances.